2013
DOI: 10.1109/msp.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Must social networking conflict with privacy?

Abstract: Online social networks (OSNs) have serious privacy drawbacks, some of which stem from the business model. Must this be? Is the current OSN business model the only viable one? Or can we construct alternatives that are technically and economically feasible?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…7,10 • Mainly those solutions suggest the OSNs architecture need to be changed. 7,10 • Mainly those solutions suggest the OSNs architecture need to be changed.…”
Section: Proposalmentioning
confidence: 99%
See 4 more Smart Citations
“…7,10 • Mainly those solutions suggest the OSNs architecture need to be changed. 7,10 • Mainly those solutions suggest the OSNs architecture need to be changed.…”
Section: Proposalmentioning
confidence: 99%
“…However, users must know that in fact service provider has the power to confidently benefit from sharing this information; and that simply because users are NOT CUSTOMERS, the ad service buyer is the customer, users are commodity. 7 Furthermore, a recent study reported that "a key factor that undermines privacy for Facebook users is the amount of information they disclose on their profiles." Additionally, some OSN user profiles are crawled by search engines, which make them (user profiles) visible to others who are not members (have no account) of the OSN.…”
mentioning
confidence: 99%
See 3 more Smart Citations